Penggunaan Sim-Rosi Berbasis PjBL dan Steam untuk Meningkatkan Keterampilan Abad 21 Bagi Peserta Didik Sekolah Dasar - AH Burhanudin (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
Teachers as the spearhead of education who are directly related to students are expected to be able to provide positive content in fostering the characteristics of 21st century learning, in the form of: critical thinking, problem solving, collaboration, and communication (4C). The purpose of these activities is to be able to equip and foster creativity, productivity, and to prepare students for the progress of the 21st century. Based on preliminary observations, it is known that learning triggers the growth of 21st century characteristics (4C) in grade 3 students of Langenharjo 2 Elementary School in the learning process. very low. Simple Rocket Design (SIM-ROSI) is a design developed as a solution to improve the quality of student learning. Developed with a 4D development research model according to Thiagarajan. Supported by the implementation of Project Based Learning (PjBl) -based learning and Engineering Science Technology Art and Math (STEAM). Development success indicators are based on observations of students' 4C activities in learning. The collected data were analyzed using descriptive analysis and statistical tests using paired sample t-test. The results of the analysis show the conclusion that SIM-ROSI based on PjBL and STEAM is very effective in increasing the 4C activities of students in thematic learning in elementary schools.